A Dergâh for the Nation: Spiritual Identity and Cultural Continuity in Occupied Istanbul (1918–1923) - Adile Sedef Dönmez (Tasavvuf Araştırmaları Enstitüsü Dergisi)
This article examines how Dergâh Journal articulated a vision of spiritual nationalism, framing national identity as a continuity from the Ottoman Empire to the Turkish Republic, grounded in cultural inheritance, artistic expression shaped by Ottoman-Sufi traditions, and a deep historical consciousness. Published during the Allied occupation of Istanbul between 1921 and 1923, Dergâh positioned itself outside the dominant nationalist paradigms of its time: on one side, militant resistance; on the other, rigid positivist modernization. Instead, it sought an alternative path to reimagine Turkish nationalism. The journal’s contributors contended that the true foundation of a nation lies not only in political structures but in the ability to preserve and reinterpret its spiritual, cultural, and artistic heritage. Rejecting both passive Western imitation and reactionary nostalgia, Dergâh pursued a dynamic synthesis of past and present, asserting that literature, art, music, and language must evolve organically while remaining anchored in their cultural and spiritual roots. Drawing inspiration from Henri Bergson’s (d. 1941) concepts of intuition (intuition) and duration (durée), the journal envisioned national identity as a living, ever-evolving force. Through its engagement with themes such as linguistic fragmentation, artistic mimicry, and the erosion of historical temporality, Dergâh sought to reclaim national consciousness by reviving a cultural and spiritual sensibility deeply rooted in Ottoman-Sufi traditions, envisioning art and thought as living continuities rather than borrowed imitations. This study situates Dergâh within the broader debates on nationalism and modernization, highlighting its distinctive attempt to reconcile spiritual depth and artistic vitality with the challenges of shaping modern Turkish identity.